A Framework for Efficient Government Investment - Warner, Andrew (IMF Working Papers; Working Paper ;, 2013)
Welfare economics, scope and performance of government, externalities, public goods, cost-benefit analysis, subsidies economize on spending without losing effectiveness by modifying the conceptual framework guiding state expenditures. The familiar framework says that state intervention is justified when the spending provides public goods or when the intervention addresses externalities, provided the social return is above a threshold. This paper argues that another consideration needs to be brought into the mix - whether, in spite of the externalities, the private sector has an incentive to undertake the activity. It is argued that these two considerations together define a more efficient framework under which to justify state intervention. According to this modified framework, even a benign state interested in social welfare would not in fact address every externality nor necessarily select expenditures with the highest social returns. These points are summarized in a graph which is then used to analyze policy rules, subsidies and effective interaction between the state and the private sector. It is hoped that this paper points to the kind of information that needs to be collected and acted upon so that states may achieve their goals more effectively.